Dietary total antioxidant capacity and risk of stroke: a systematic review and dose–response meta-analysis of observational studies - Huang, Yiqian; Ni, Yajun; Yu, Lin; Shu, Long; Zhu, Qin; He, Xingzhen (Frontiers in Nutrition, 2024)
Background: Previous studies have reported the association between dietary total antioxidant capacity (TAC) and risk of stroke, but these findings have been inconsistent.We therefore performed this systematic review and dose-response meta-analysis of observational studies to evaluate the association between dietary TAC and risk of stroke.Methods: A systematic literature search was carried out through PubMed, ISI Web of Science, EBSCO, Scopus and China National Knowledge Infrastructure (CNKI) databases, to find the relevant articles published up to 31 May, 2024. Random-effects or fixed-effects models were used to pool the relative risks(RRs) and their 95% confidence intervals(CIs) where appropriate.Heterogeneity across studies were determined using the Cochran's Q test and I-square(I 2 ) statistics.Results: Eight observational studies (six cohort and two case-control studies) were included in the final analysis. The pooled results showed that higher intake of dietary TAC was associated with a lower risk of stroke (RR=0.88; 95%CI: 0.81-0.95, P=0.002). Additionally, dose-response analysis of cohort studies demonstrated a linear association between dietary TAC intake and risk of stroke (RR=0.994; 95%CI: 0.990-0.999, Pnonlinearity=0.329, Pdose-response=0.014). Subgroup analyses showed the inverse association between dietary TAC intake and risk of stroke in the studies with mean age<50 (RR=0.82, 95%CI: 0.67-0.99, P=0.044), and there was no evidence of heterogeneity (P=0.360; I 2 =0.0%). Conclusions: Our findings indicated that higher intake of dietary TAC was inversely associated with the risk of stroke. Future studies in particular of longitudinal design are needed to confirm this inverse relationship.